Never say genius - Gutman, Dan. (New York : Harper, 2012)
As their cross-country journey with their parents continues through the midwest, twins Coke and Pepsi, now thirteen, again face strange assassins at such places as the first McDonald's restaurant and Cedar Point amusement park.
Keywords: Genius -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Twins -- Juvenile fiction; Assassins -- Juvenile fiction; Recreational vehicles -- Juvenile fiction; Families -- Juvenile fiction; Adventure stories